THE ROLE OF SILICON TO INCREASE ARSENIC TOLERANCE IN RICE (Oryza sativa L.) SEEDLINGS BY REINFORCING ANTI-OXIDATIVE DEFENSE (Bioagro, 2020)
Arsenic is a toxic metalloid which can cause severe problems to plants. On the other hand, silicon is a beneficial element, which supports plants to build resistance under stressed conditions. The objective of the present study was to assess the effect of silicon and arsenic on the various enzymatic, and non-enzymatic antioxidants, in shoots and roots of two rice seedlings (Du-WT and DU-OE), for one and two weeks. Seedlings were exposed to four different culture media: a) Control; b) 0.70 mM Si+no As; c) 30 μM As+no Si; d) 30 μM As+0.70 mM Si. Culture media and rice genotypes were arranged in a 8-treatment factorial with three replications. Results showed that response to silicon, arsenic and or combination of them in unstressed rice plants followed similar patterns, and varied depending upon the antioxidant. The addition of As always decreased the values, but together with silicon there was a partial recovery of them. The pattern of plant response was similar regardless the plant tissue or time of exposure to As. Transgenic Dullar rice, under As stress conditions, activated the highest level of antioxidants, especially when seedlings were treated with silicon.
Keywords: Antioxidants; enzymes; plant resistance; toxic element